Pharmacodynamics of Vancomycin for the Treatment of Experimental Penicillin- and Cephalosporin-Resistant Pneumococcal Meningitis - Ahmed, Amina (American Society for Microbiology, 1999)
With the emergence of β-lactam antibiotic resistance among strains of Streptococcus pneumoniae, vancomycin has assumed an important role in the treatment of bacterial meningitis. Using the rabbit meningitis model, we evaluated the pharmacokinetics and pharmacodynamics of vancomycin in this setting. Animals were given 80 mg/kg of body weight daily in two or four divided doses to determine the penetration and activity of vancomycin in cerebrospinal fluid (CSF); each regimen was administered with and without dexamethasone. Mean peak (2 h) concentrations in CSF that were four- to eightfold higher than the minimum bactericidal concentration (MBC; 0.5 μg/ml) for the pathogen were adequate for bacterial clearance. In both groups concentrations in CSF remained higher than the MBC for greater than 80% of the respective dosing intervals, and the penetration of vancomycin into CSF was 20%. Mean concentrations in CSF at 24 to 36 h of therapy were lower than those achieved during the first 12 h, consistent with a decline in the level of antibiotic entry into CSF as inflammation wanes. Rates of bacterial clearance were similar for the two regimens, and for all animals cultures of CSF were sterile by 36 h. The coadministration of dexamethasone significantly reduced the penetration of vancomycin into CSF by 29% and significantly lowered the rate of bacterial clearance during the first 6 h in animals receiving 20-mg/kg doses of vancomycin. For animals receiving 40-mg/kg doses, therapeutic peak concentrations in CSF were obtained even with steroid use, suggesting that the effect of steroids may be circumvented by the use of larger daily doses of vancomycin.